Multi-scale in situ mechanical investigation of the superelastic behavior of a Cu–Al–Be polycrystalline shape memory alloy. (15th August 2022) - El Hachi, Y.; Berveiller, S.; Piotrowski, B.; Wright, J.; Ludwig, W.; Malard, B.
Abstract: The superelastic behavior of a Cu–Al–Be alloy was studied in situ during tensile tests combining two high-energy synchrotron techniques. The initial microstructure was reconstructed using diffraction contrast tomography; the elastic strain and stress tensors of each individual grain were then determined using a 3D X-ray diffraction microscopy technique. The alloy was heat-treated until coarse grains formed, and the probed volume fraction was limited to ∼ 200 grains. The mean grain size, as estimated from both techniques, agreed well with that determined by optical microscopy, i.e., approximately 130 µm. During the early stage of the martensitic transformation (MT), 187 grains with strong stress heterogeneities were detected in the elastic domain; in particular, the stress values along the tensile direction varied by a factor of three between different grains. The reconstructed 3D microstructure served as input data for finite element modeling, wherein a micromechanical approach factoring in the martensitic transformation was used to simulate the in situ tensile tests. The coupled numerical and experimental tensors of the 187 grains confirmed strong stress heterogeneities between them. The influence of the position and crystallographic orientation of the neighboring grains were also examined. Graphical abstract: Image, graphical abstract